Facilitating Secure Query Processing on Encrypted Databases on the Cloud - Ben Omran, Osama M.; Panda, Brajendra (2016 IEEE International Conference on Smart Cloud (SmartCloud), 2016)
Many features and advantages have been brought to organizations and computer users by Cloud computing. Many applications and services have been distributed by Cloud providers in an economical way. Even though companies and clients have started using Cloud computing, they are still concerned about their data's security because the data are stored and controlled by the Cloud providers [9]. In this paper, a technique has been explored to improve query processing performance while protecting database tables on a Cloud by encrypting those so that they remain secure. In addition, four techniques have been designed to index and partition the data, and these indexed data will be stored together with the encrypted table on the Cloud or server. The indexes and partitions of the data are used to select part of the data from the Cloud or outsource data depending on the required data. The indexed data can be used to increase the performance when the data are requested from the encrypted table. To compare the efficiency of our proposed methods, results will be presented in forms of graphs. In addition, the paper will explain how to improve performance by combining the two methods to partition the data.